Psycare - Mobeen Nazar,; Faisal Jabbar,; Ayesha Anees Zaveri, (Journal of Computing Technologies and Creative Content, 2022)
Communication plays important role in every aspect; it can also be helpful in the treatment of diseases whether they are physical disease or mental problems. The disease known as psychosis is a mental disorder that needs frequent meetings of psychologists and patients. Information technology is shifting modern society to help to do tasks more efficiently. The authors are providing the solution of information services to help psychologists to bein touch with patients more efficiently and more easily. For making this easy a mobile application is developed for the patient to communicate well with the psychologist. The application will get the data from the patient on regular basis automatically and send the data to his/her psychologist so that later can be used for better treatment.